Effectiveness of a Piezoelectric-Assisted Distraction Osteogenesis Procedure for the Treatment of Ankylosed Permanent Front Teeth. Issue 4 (June 2019) - Ramaglia, Luca; Cicciù, Marco; Fiorentino, Emilio; Saviano, Raffaele; Blasi, Andrea; Cervino, Gabriele; Isola, Gaetano
Abstract : Abstract: A common complication of tooth replantation after traumatic avulsion is tooth ankylosis causing dental malpositioning, partial loss of function, tipping of adjacent teeth and worsening of aesthetics. The aim of this study is to evaluate the effects of a repositioning procedure of such ankylosed permanent front teeth by a distraction osteogenesis procedure. Five patients (mean age 13.4 years), with an ankylosed permanent front tooth in the anterior area, were enrolled in the present study. After the pre-operatory orthodontic preparation, each selected site was treated with single-tooth dento-alveolar block osteotomy surgery performed with a piezoelectric surgery device with ultrasonic cuts on the buccal side. Subsequently, a custom distraction device, made by a resin splint and a sector expansion screw, was set in such a way it delivered a force with direction and sense towards the planned position of the tooth as well as the osteotomy's incision. After a latency period of 14 days, the distraction of the dento-alveolar block was started with a rate of distraction of 0.8 mm per day. The average shift obtained by the ankylosed teeth was 7.8 ± 0.75 mm (±SD), and the ankylosed tooth was regularly positioned into the occlusion in 20.4 ± 1.85 days (±SD), with a slight relapse (±0.5 mm) observed after 1 year. This study indicates that a therapeutic approach combining piezoelectric surgery and orthodontic therapy may be useful for the treatment of ankylosed permanent teeth in the frontal area with a long-term follow-up over 5 years.